BRAZILIAN ECONOMY: FOUR DECADES OF NEAR STAGNATION - Marchetti, Adalmir; Donadio Miebach, Alessandro (Brazilian Keynesian Review, 2023)
The article discusses the four decades of near stagnation and the possibilities of resuming economic growth in the Brazilian economy. While in the central countries there are indications of the abandonment of many central elements of neoliberalism, in Brazil there was the adoption of a late neoliberalism after 2016. The necessary condition for the resumption of economic growth in Brazil economy is the overcoming of late neoliberalism with the construction of a new social consensus.